Investigation on protective effects of Cressa cretica extract in scopolamine- induced memory impairment - Khare, Pragati; Yadav, Ghanshyam; Chaudhary, Sudhir; Singh, Lubhan (International Journal of Pharmacology and Toxicology, 2013)
The present study was undertaken to investigate the effects of Cressa cretica on learning and memory in mice. Elevated plus maze and passive avoidance paradigm were utilized to test learning and memory. Two doses (200 and 400 mg/kg, p.o.) of ethanolic extract were administered for 28 successive days in separate group of animals. The dose of 400?mg/kg p.o. of CCE (Cressa cretica extract) significantly improved learning and memory of mice. Furthermore, this dose significantly reversed the amnesia induced by Scopolamine (0.4 mg/kg, i.p.). To find out the mechanism by which CCE exerts nootropic activity, the effect of CCE on whole brain AChE activity was also estimated. CCE also decreased whole brain acetyl cholinesterase activity. Antioxidant properties and presence of flavonoids in Cressa cretica may be contributing to memory enhancement effect. Here, Piracetam (200 mg/kg, i.p) was used as a standard nootropic agent. Hence Cressa cretica appears to be a promising candidate for improving memory and it would be worthwhile to explore the potential of this plant in the management of dementia and Alzheimer’s disease. However, further studies are necessitated to identify the exact mechanism of action.   Keywords: Cressa cretica, Alzheimer’s disease, Central nervous system (CNS), Elevated plus maze, Passive avoidance apparatus.